(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This research study is conducted in order to identify the various factors and impact of information technology in business process reengineering which are essential to make the rethinking and radical changes in the production and manufacturing industry, the main objective of this research study is to reduce the costs of the resources, improvement working style of employees and efficiency which leads to the organizational development to the be the world level competitors. In this research study the researcher developed the qualitative and quantitative distinction between business process reengineering parameters and information technology, there are number of benefits after successful implementation of this methodological concept in production and manufacturing industries such as empowering employees, eliminating waste and unnecessary management overhead and identification of inefficient processes which makes barriers in organizational development. Today the organizations have to consider about their structure and development in different dimensional phases, it is dynamically and rapidly changing environment, which uses new technology and resources at different significant level. Furthermore, outcome of business process reengineering future and appraisal can be more successful by combining with information technology and its advances for developing the business organization. The researcher strongly recommended that the role of information technology and technology advances in business process reengineering are significant and can be used for radical change, devise new ways of thinking, and better support the functionality of organization.